PENINGKATAN PENGETAHUAN ORANGTUA TENTANG KESEHATAN MENTAL REMAJA MELALUI PENDIDIKAN KESEHATAN DI WILAYAH KERJA PUSKESMAS CIANJUR KOTA - Hartati, Sri; Fauziah, Sifa; Qurrotu’aini, Hasna Aqilla; Nurhayati, Evi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2022)
Adolescent health problems, in addition to physical impacts, can also affect mental health, emotional, economic and social well-being. Mental health problems are as important as physical health problems. Psychiatric changes during adolescence include emotional changes, and intelligence development. Community Service with the title Increasing Parents' Knowledge of Adolescent Mental Health through Health Education in the Cianjur City Health Center Working Area. This Community Service (PkM) activity was carried out in the Cianjur City Health Center Working Area. The method used in this community service activity is health education. The final results of this activity show an increase in results from the pre test to the post test, this is because families have been given knowledge about mental health in adolescents.